El desarrollo sostenible y la teoría del derecho internacional - Carlos Fernández-Liesa (Revista Iberoamericana de Estudios de Desarrollo)
The scientific object of this contribution is an approach to Sustainable Development Goals (SDG) (and to sustainable developments) from the point of view of international law theory. We address the notion, functions and conception of public international law and the main theories in the context of SDG, as well as from the perspective of main discussions.